2020
DOI: 10.7759/cureus.10197
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Outcomes From Standalone Minimally Invasive Surgery-Transforaminal Lumbar Interbody Fusion Patients in an Ambulatory Surgery Center vs. Hospital Setting

Abstract: We sought to evaluate differences in perioperative baseline characteristics, operative efficiency, and 30-day safety events for patients undergoing standalone minimally invasive surgery-transforaminal lumbar interbody fusion (MIS-TLIF) in a hospital versus an ambulatory surgery center (ASC). Methods Patients were retrospectively identified and sequentially enrolled from the office records of a single, community neurosurgeon. Records for the first 50 qualifying patients in the hospital and ASC cohorts were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 22 publications
(38 reference statements)
4
24
0
Order By: Relevance
“…This multi-center study extends previously reported single-center findings [ 9 ], and provides procedural and 30 day safety outcomes for patients having a minimally-invasive TLIF procedure with the stand-alone VariLift ® -LX expandable interbody fusion device in the ASC compared to the traditional hospital setting.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This multi-center study extends previously reported single-center findings [ 9 ], and provides procedural and 30 day safety outcomes for patients having a minimally-invasive TLIF procedure with the stand-alone VariLift ® -LX expandable interbody fusion device in the ASC compared to the traditional hospital setting.…”
Section: Introductionsupporting
confidence: 80%
“…Indeed, Heemskerk et al [ 8 ] recently reported that patients treated with minimally-invasive TLIF have similar two-year clinical outcomes as patient having open TLIF. Correspondingly, findings have been reported demonstrating the feasibility, safety and clinical utility of performing the TLIF procedure in the ASC [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 85%
“…Blaginykh et al 19 investigated the NSQIP database and found that outpatient PLF patients were younger and less likely to be receiving steroid therapy, but were more likely to have high BMI and diabetes. Schlesinger et al 21 reported on ambulatory MIS-TLIF patients and found that they were younger, had fewer comorbidities, and had superior functional status. Kim26 reports similar findings for TLIF patients indicating those younger than 72, BMI <35, ASA class 2 or lower, preoperative ODI <50, with adequate home care, and no daily preoperative opioid use were selected for outpatient surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The drains would be removed in the clinic setting at approximately one to five days postoperatively. 21 Parrish and colleagues perioperative plan included education/ counseling and administered 10 mg cyclobenzaprine, 150 mg pregabalin, and 10 mg oxycodone one hour preoperatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Outpatient spine surgery in particular has markedly grown in volume over the past decade. [13][14][15] A recent study by Lenke et al 16 examining the use of ASCs in the Medicare population found a 1780% increase in the volume of outpatient spinal surgeries from 2012 to 2017. This was more than 5 times higher than that of any other orthopedic specialty.…”
mentioning
confidence: 99%